An analysis of the distribution of hetero- and isodisomic regions of chromosome 7 in five mUPD7 Silver-Russell syndrome probands. Issue 6 (1st June 1999) - Preece, M A; Abu-Amero, S N; Ali, Z; Abu-Amero, K K; Wakeling, E L; Stanier, P; Moore, G E
Abstract : Silver-Russell syndrome (SRS) shares common features of intrauterine growth retardation (IUGR) and a number of dysmorphic features including lateral asymmetry in about 50% of subjects. Its genetic aetiology is complex and most probably heterogeneous. Approximately 7% of patients with SRS have been found to have maternal uniparental disomy of chromosome 7 (mUPD7). Genomic DNA samples from five SRS patients with mUPD7 have been analysed for common regions of isodisomy using 40 polymorphic markers distributed along the length of chromosome 7. No regions of common isodisomy were found among the five patients. It is most likely that imprinted gene(s) rather than recessive mutations cause the common phenotype. Heterodisomy of markers around the centromere indicated that the underlying cause of the mUPD7 is a maternal meiosis I non-disjunction error in these five subjects.